Kajian Pemanfaatan Silika dari Sekam Padi dalam Pengolahan Limbah Tekstil - Masrofah, Isma (Universitas Suryakancana, 2017)
Abstract – Textile industry is one of the waste contamination industries that can pollute the environment, so that the rapid development of textile industry must be followed by the improvement of its sewage treatment system. Along with the global issue of Green Manufacturing, the textile industry waste treatment can promote environmentally friendly waste treatment process and derived from renewable substances. Therefore, it is necessary to study the utilization of rice husk silica in the processing of textile waste. The results of the study provide information that textile wastes come from all processes in the textile industry, from pretreatment to finishing. Rice husk ash silica is a material utilized adsorption of textile waste or mixture of PolyVinylChloride (PVC) membrane material to filter textile waste. The characteristics of rice husk silica are influenced by the extraction method. The initial washing process using acid and then combustion at 600 ° C - 750 ° C produces a relatively high purity of silica with a maintained silica amorphous level.Keywords: Rice Husk Silica, Textile Waste, Textile Waste Processing, Silica Characteristic